Comparative study of social studies curriculum in scandinavian countries in developing students' social skills - Fathimah, Siti; Tenri, Andi; Sasea, Sanita Carolina; Marleni, Marleni; Suarjana, I Wayan Gede (Intelektual Pustaka Media Utama, 2024)
Social skills play a central role in shaping individuals who are able to adapt and contribute to society. This article analyzes the comparative social studies curriculum in Scandinavian countries (Denmark, Norway and Sweden), focusing on how students’ social skills are developed through their approach to learning. The research method used is a qualitative approach with an emphasis on document analysis and uses a horizontal descriptive approach in the context of comparative education. The results of the comparison found that Denmark emphasizes the integration of social skills in practical learning and research projects, Norway through an integrated approach with its contemporary issues while Sweden applies innovation through technology and community involvement. The comparison between the three countries revealed similarities, differences, as well as challenges and successes in the development of students’ social skills. The conclusions of this analysis provide a foundation for recommending best practices and improvements in social studies curriculum, which can be applied globally to enhance students’ social skills development in this modern era.